PENGARUH MEDIA PENDINGIN TERHADAP KARAKTERISTIK MEKANIK DAN STRUKTUR MIKRO PADA PELAT BAJA KARBON RENDAH - Wicaksono, Iskandarsyah; Ismarwanti, Sri; Setiawan, Jan; Susetyo, Ferry Budhi; Syamsuir (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Low carbon steel has high ductility and is easy to shape, so it is widely used in industry and construction. However, this material has low mechanical strength and hardness, so it is easy to wear. Mechanical properties can be improved by heat treatment, namely heating at a specific temperature and holding it for some time and then cooling. Cooling media will affect the level of enhancement in its mechanical properties. Therefore, in this study, observations were done on the mechanical characteristics and microstructure of low carbon steel after heat treatment and cooling on various cooling media. The heating process was carried out at a temperature of 950 °C with a holding time of 15 minutes. The sample is then cooled with a variety of coolants (aqua dest, cooking oil, oil and open-door furnace). The results of the observations on samples of low carbon steel plates (0.0524%) shows that the sample without heat treatment has the highest stress value of 375.75 MPa and the open furnace door cooling has the lowest stress value of 200.53 MPa. The highest strain value occurred in the open-door cooling of 38.77% and the lowest strain value of 25.49% occurred in the cooling with cooking oil. Observation on the material’s microstructure before and after heat treatment shows ferrite and pearlite.